On computing relative effective population size estimates and parameters from an equilibrium cycle of hermaphrodite frequency fluctuation due to mixed reproductive modes in filamentous fungi - Christopher Toomajian (Fungal Genetics Reports, 2021)
Many filamentous ascomycete fungi reproduce primarily asexually, with only occasional sexual generations. This can lead to a departure from the 1:1 mating type ratio that is expected in obligate sexual populations. The relaxed selection on sexual traits also can lead to a decrease in the frequency of female fertile strains in field populations, while male fertility does not similarly decrease since male gametes also can serve as asexual spores. Both changes ultimately impact the strength of genetic drift in populations. The frequency of female sterility likely increases with the time since the last generation of sexual reproduction, such that it can be used to estimate the relative frequency of sexual reproduction. Here I provide additional details relevant to Leslie and Klein’s (1996) model of mixed sexual reproduction and vegetative propagation as related to the frequency of female sterility. This includes new or modified equations that allow for simpler calculations of i) two estimates of relative Ne, ii) the expected range of hermaphrodite frequencies during the cycles of mixed reproduction, and iii) the relative frequency of sex. These equations also are included in spreadsheet templates into which researchers can directly enter frequencies computed from their population data to estimate these parameters for their own populations. These resources will make the results of Leslie and Klein (1996) more accessible and should increase the use of this model in evaluating the frequency of sexual reproduction of filamentous fungi.
Keywords: sexual reproduction; asexual reproduction; female sterility; recombination; fungal mating-type idiomorphs